2018
DOI: 10.3390/su10030796
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Adaptation Tools at the Community Level: An Integrated Literature Review

Abstract: The negative impacts of climate change are experienced at the global, regional and local levels. However, rural communities in sub-Saharan Africa face additional socio-political, cultural and economic challenges in addition to climate change. Decision support tools have been developed and applied to assist rural communities to cope with and adapt to climate change. However, poorly planned participatory processes and the lack of context-specific approaches in these tools are obstacles when aiming at strengtheni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 77 publications
1
14
0
1
Order By: Relevance
“…Intercultural and participative management also faces the challenge of integrating Indigenous knowledge with scientific-academic knowledge, using the capacities and expertise of institutions to promote sounded and unprejudiced participative research over socio-environmental conditions that revolve around Indigenous fire management and application [24,25,28,29,31,34,35,86,87,95].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intercultural and participative management also faces the challenge of integrating Indigenous knowledge with scientific-academic knowledge, using the capacities and expertise of institutions to promote sounded and unprejudiced participative research over socio-environmental conditions that revolve around Indigenous fire management and application [24,25,28,29,31,34,35,86,87,95].…”
Section: Discussionmentioning
confidence: 99%
“…Indigenous people also expressed the importance of the support of firefighters and academics to plan safer burning conditions and the acquisition of training and tools to prevent the spread of uncontrolled fires. All participants agreed on the adaptive value of working and learning together to develop a new fire management paradigm that integrates the efforts, knowledge, and capabilities of Indigenous people with governmental institutions and academics [29,34,96].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platforms and related resources to support climate change adaptation have become widely available in recent years, and examples can be found for most sectors and for different geographical locations, including coasts (Torresan et al 2016;Lane et al 2013) and rural areas (Cao et al 2018;Nkoana et al 2018). Despite the widespread availability of decision support resources, there is little understanding of their effectiveness-the extent to which they are useful to practitioners, and the extent to which they are used.…”
Section: Discussionmentioning
confidence: 99%
“…Without these in place, the process might not have succeeded. In considering which resources can and cannot be adapted, it should be recognised that some have suggested that decision-support resources that are context-specific and targeted perform better than those that seek to address more general requirements (Förster et al 2015;Cortekar et al 2016;Nkoana et al 2018) and it is perhaps less likely that the latter would lend themselves well to such adaptation and translation.…”
Section: Translation and Adaptationmentioning
confidence: 99%